Composition and Antimicrobial Activity of the Essential Oil of Spilanthes paniculata Growing Wild on the Gaoligong Mountains, China - Zhu, S.M.; Zhu, L.; Tian, Y.J.; Yin, Y.C. (Asian Journal of Chemistry, 2011)
The essential oil obtained by hydrodistillation of Spilanthes paniculata obtained from Gaoligong Mountains, China was analyzed by gas chromatography and gas chromatography/mass spectrometry (GC/MS), simultaneously. Main constituents of the oil was found as E-g-cadinene (10.64 %), b-caryophyllene (6.31 %), thymol (5.55 %), b-pinene (5.42 %), 1,8-cineole (4.28 %), p-cymene (3.56 %) and bicyclogermacrene (3.17 %). The essential oil was also screened for its antimicrobial properties against various pathogens.